(untitled) (International Seven Journal of Multidisciplinary, 2025)
Brand a company allows to differ it from the others ones and be distinctive by consumers. In this way, the organizations that work to maintain a position through having a brand obtain competitive advantages over others which simply engage in marketing their products or services in a traditional way. On the other hand, innovation is the added value of any brand, which allows to differentiate it from the competition moreover. The main objective of this research is to find out the perception that Santander’s young people have of the brand Youth without DNA, moreover to know how feasible is it to sell customized products looking for brand positioning. This investigation is carried out through a sample of 384 students between 14 and 28 years. The statistical techniques used were descriptive and multivariate ANOVA to demonstrate the relationships between the variables. The results show a level of acceptance by young people to Juventud sin ADN-branded item consumption. Detected that customers of the brand perception is oriented towards the identification of your preference, the type of potential client products, distribution channels chosen by persons investigated and analyze aspects of higher influence at the time of purchase of a young client. Finally, proposed improvements to take advantage of the brand in a more competitive way.